A divulgação das informações sobre modelos de negócios e seus reflexos na agregação de valor das empresas no Brasil - Alves, Paulo César Barbosa (Universidade do Vale do Rio dos Sinos, 2022)
In view of the growing interest in the Business Model (BM) theme in the accounting literature, in response to texts issued by international standardization bodies such as the IASB - International Accounting Standards Board, FRC - Financial Reporting Council and the EFRAG - European Financial Reporting Advisory Group, which consider the concepts of BM, this study aims to analyze the contribution of practices of voluntary disclosure of information about the business model in the aggregation of value of companies in Brazil, from the perspective of Information Asymmetry. The sample of companies listed in the Brazil Amplo Index (IBrA) of B3 from 2015 to 2021 was used, analyzing the behavior of the MN disclosure indices and the information asymmetry index (IAI), and its reflections on the cost of capital and value of companies, through multiple linear regressions. The results showed that the disclosure of MN information contributes to the mitigation of information asymmetry, in the reduction of capital costs, impacting the valuation of companies and that the IAI presents positive results regarding the perception of analysts about the disclosure of information in the companies. companies. The results corroborate the hypotheses of this study, contributing to the academic literature on disclosing information and mitigating asymmetries, and their impact on financial indices, as well as demonstrating the importance of disclosure about BM, as part of a research group that seeks to measure the benefits of companies having reports that include the disclosure of the value chain, which facilitates decision-making on investing in companies and/or disclosing the services provided to society.
Keywords: Modelo de negócios; Assimetria da informação; Custo de capital; Valor das empresas; Cost of capital; Value of companies; Business model; Information asymmetry; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis